2006
DOI: 10.1002/jqs.1007
|View full text |Cite
|
Sign up to set email alerts
|

Holocene marine terraces on two salt diapirs in the Persian Gulf, Iran: age, depositional history and uplift rates

Abstract: Slightly inclined Holocene marine terraces cover parts of two circular salt diapirs (Hormoz and Namakdan) in the Persian Gulf. Their relative altitude above present sea level results from a combination of general marine transgression/regression affecting the whole area, and of local uplift related to salt diapirism. Differential uplift rate of the studied diapirs in centre-to-rim profiles was calculated from results based on: (i) radiocarbon ages of skeletal remains of benthic faunas (19 samples), which origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
(53 reference statements)
3
54
0
Order By: Relevance
“…The thickness of the Holocene residuum attains only a few meters, indicating that the rock salt was protected from seawater only by a few meters of material. Dating of the Holocene marine terraces indicated that submarine residuum formation occurred in the period of 9-6 kyr BP (Bruthans et al, 2006). Fig.…”
Section: Weathering Residuum Covermentioning
confidence: 97%
See 1 more Smart Citation
“…The thickness of the Holocene residuum attains only a few meters, indicating that the rock salt was protected from seawater only by a few meters of material. Dating of the Holocene marine terraces indicated that submarine residuum formation occurred in the period of 9-6 kyr BP (Bruthans et al, 2006). Fig.…”
Section: Weathering Residuum Covermentioning
confidence: 97%
“…They consist mostly of detrital limestone, gravels and carbonate mud. Bruthans et al (2006) described these sediments in detail.…”
Section: Sedimentary Covermentioning
confidence: 98%
“…The U-series age is 350-250 kyr BP, however, the samples N8 have been recrystallized to calcite and the ages are not conclusive (compare with Pirazzoli et al, 2004). The SE margin of the Namakdan diapir is covered by a 10 m-thick Holocene marine terrace 5-8 cal kyr BP in age (Bruthans et al, 2006a).…”
Section: Submarine Residua and Marine Depositsmentioning
confidence: 95%
“…The central part of the diapir is ∼120 m a.s.l. The southern marginal zone of the island is formed by sub-vertical strata of Miocene siliciclastics overlain by an angular unconformity of Pleistocene deposits (IOOC, 1969;Bruthans et al, 2006a). The surface of the diapir is mostly covered with thin weathering residua (Bruthans et al, 2000(Bruthans et al, , 2009.…”
Section: Geographical and Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation